178k views
4 votes
Please look at the picture and help me with this question

Please look at the picture and help me with this question-example-1
User RAAC
by
6.2k points

1 Answer

3 votes

Answer:

Explanation:

f(x) = 4^x

g(x) = f(x -1) + 3

g(x) = 4^(x - 1) + 3

See the diagram that is below.

Red line: f(x) = 4^x

Blue line: g(x) = f(x - 1) + 3

The graph has been transformed so that f(x) moves upwards by 3 unitsw to get to g(x)

Furthermore, if x = 0 the y intercept for f(x) = 1

If x = 0 then g(x) moves up 3 spaces by virtue of the 3, and and up another 1/4 because the first term becomes 4^-1 = 1/4. This 1/4 gets added to the 3 to give 3 1/4

Please look at the picture and help me with this question-example-1
User Edson Menegatti
by
5.3k points